SISTEM PREDIKSI TINGKAT KRIMINALITAS MENGGUNAKAN METODE TRIPLE EXPONENTIAL SMOOTHING: STUDI KASUS PADA POLRES KABUPATEN PROBOLINGGO - Arwin Datumaya Wahyudi Sumari; Ricky Yulian Adi Pratama; Odhitya Desta Triswidrananta (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
Criminality is all forms of action and conduct that violate the law as well social and religious norms that are detrimental to the society both economically and psychologically. The emergence of verious crime forms with new dimension recently shows that the criminality is always developing. In the effort to reduce the increase of the crime rate, a crime action prediction system is needed to anticipate the future. In this research a crime rate prediction system based in the types of criminal action using Triple Exponential Smoothing (TES) method has been developed, and the prediction accuracy of the system is measured by using Mean Absolute Percentage Error (MAPE) method with a case study on Resort Police of Kabupaten Probolinggo, East Jawa. From the conducted test, obtained results MAPE score of theft by weighting (Curat) type is 7% or Very Accurate prediction criterion. MAPE score for crime action type Others, motor vehicle theft (Curanmor), Destruction, and Fraud are 9.8%, 14.4%, 13.6%, and 16%, or Good prediction criterion. For crime action type Beatings, violent theft (Curas), severe persecution (Anirat), Murder, and Thief each one has MAPE score 23.2%, 31.2%, 21.2%, 33.2%, and 50%, or Reasonable prediction criterion, while MAPE score for Animal Theft is 92% or Inaccurate prediction criterion. In general, the criminality rate prediction system using TES method that has been developed for the case study on Resort Police of Kabupaten Probolinggo obtains MAPE score 28,3% or Reasonable prediction criterion.